ALGA HIJAU (CHLOROPHYCEAE) YANG DI TEMUKAN DI SALAH SATU SUNGAI DI PROVINSI SUMATERA BARAT (Universitas PGRI Sumatera Barat, 2020)
This study aims to identify green algae (Chlorophyceae) in Asik stream, Kanagarian Lubuk Layang, Rao District, Pasaman Regency .Identification is done at Botanical Laboratory of the Biology Education Study Program STKIP PGRI West Sumatra. This research uses deskriptive survey method. Sampling is carried out direcly on the streams, the technique used is purposive sampling based on environmental conditions in the sreams, by establishing three research stations. From the results of the research, there were 15 species of Chlorophyta in the Asik Streams, include 4 ordo that is Chlorococcales 3 species, Cladophorales 2 species, Oedogoniales 1 species and Zygnematales 9 species. Stream chemical physics factor that are in the normal range to support Chlorophyta life.